Developing Green Tourism-Based Model of Information Technology Utilization in Tourism Villages - Ni Luh Ayu Kartika Yuniastari Sarja; I Putu Krisna Arta Widana; Putu Adi Suprapto; Tyas Rahajeng Pamularsih (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
The purpose of this study is to develop a model for the use of information technology in Tourism Villages by mapping the use of information technology on all aspects of tourism villages based on the concept of green tourism that focuses on environmental preservation and community welfare. The method used in this research is an information research framework consisting of stages of literature review and environmental aspects, analysis, construct identification, model development, model evaluation, and model application methods. The results of the research are in the form of a model for the use of information technology in green tourism-based tourism villages along with the method of applying the model. This model consists of two connected constructs, namely the use of information technology and green tourism. The implementation of this model in tourist villages is explained in the method of applying the model which contains a mapping of information technology needs and implementation steps based on the classification of tourist villages, namely pioneering, developing, advanced and independent. This model can be used as a reference for tourism village managers in utilizing information technology according to their needs.